Understanding Amy Lau's Depression and Coping Strategies Depicted in Lee Sung Jin's Beef - Hidayati, Nur Laily (Universitas Negeri Surabaya, 2024)
Directed by Lee Sung Jin, the miniseries Beef (2023) portrays the story of Amy Lau, who suffers from depression because she tends to repress her emotions and desires. She employs several strategies to cope with her stressors. Therefore, this article purposely attempts to find out Amy's depression and the coping strategies used to deal the stressors. In analyzing her depression, this study employs Jacques Lacan's Mirror Stage and Symbolic Order to reveal the main character's identity process that can lead to depression. This study also uses Lazarus and Folkman's (1986) Transactional Model of Stress and Coping to reveal Amy's cognitive appraisal and coping strategies. Applying the film study research method, the researcher will focus on the behaviors, dialogues, scenes, and character's expressions throughout the miniseries. The result indicates that Amy's struggle with depression stems from her unfulfilled desires. In overcoming her stressors, Amy uses several coping strategies, such as self-controlling, focusing on and venting emotions, escape avoidance, seeking social support, planning, positive reappraisal, and acceptance.